PENGARUH PROFITABILITAS, SOLVABILITAS, DAN OPINI AUDIT TERHADAP AUDIT DELAY UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERATING (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2015-2019) - Annisa Fadhillah; Karya Satya; Liza Novietta (Studia Economica : Jurnal Ekonomi Islam, 2022)
This study aims to determine the effect of profitability, solvency and audit opinion on audit delay with compaby size as a moderating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2019 period. The sample in this study were 40 manufacturing companies listed on the Indonesia Stock Exchange in the 2015-2019 period. The data analysis technique used is multiple linear regression analysis with statistical data processing using SPSS version 20.0 data processing application.The results of this study indicate that profitability and solvency have no effect on audit delay, however, audit opinion has been shown to have a positive and significant effect on audit delay. The MRA test results show that company size is able to moderate the relationship between the effect of profitability, solvency and audit opinion on audit delay.